Dynamic modelling and optimization of an LNG storage tank in a regasification terminal with semi-analytical solutions for N2-free LNG. (6th April 2017) - Effendy, Surya; Khan, Mohd Shariq; Farooq, Shamsuzzaman; Karimi, Iftekhar A.
Highlights: Detailed model for the dynamic simulation of an LNG storage tank in a regasification terminal. Disequilibrium between the liquid and vapour phases and transfer line cooling via LNG recirculation as in reality. Semi-analytical solution for computing boil-off gas (BOG) amount for N2 -free LNG. Results on optimally designing tank and recirculation line for a desired objective such as BOG minimization. Abstract: A comprehensive dynamic model for an LNG storage tank in a typical regasification terminal, operating in holding mode, is presented. The model incorporates LNG recirculation for cooling the transfer lines for loading/unloading. It assumes a hypothetical thin vapour interface in equilibrium with the liquid to compute LNG evaporation, which allows the boil-off gas to be hotter than the tank LNG, as observed in practice. A numerical procedure based on the secant method is implemented in MATLAB for solving the governing ordinary differential equations. For the special case of N2 -free LNG, a semi-analytical solution is proposed to solve the dynamic model for this relatively complex system and compute the amount of boil-off gas (BOG). The semi-analytical solution is subsequently used to optimize the LNG storage tank and recirculation loop designs.